Answer:
4
Step-by-step explanation:
=
((6561)x(2^{-5})x(9^{0}))^{-2}x((2^{-2}/3^{3}))^{4}(3^{28})=
(6561)x(1/32)x(9^{0}))^{-2}x((2^{-2}/3^{3}))^{4}(3^{28})=
(6561/32)x(9^{0}))^{-2}x((2^{-2}/3^{3}))^{4}(3^{28})=
(6561/32)x(1)^{-2}x((2^{-2}/3^{3}))^{4}(3^{28})=
(6561/32)^{-2}x((2^{-2}/3^{3}))^{4}(3^{28})=
(1024/43046721)x((2^{-2}/3^{3}))^{4}(3^{28})=
(1024/43046721(
/3^{3})^{4}(3^{28})=
(1024/43046721(
/27)^{4}(3^{28})=
(1024/43046721(1/108)^{4}(3^{28})=
(1024/43046721(1/136048896)(3^{28})=
(4/22876792454961)x(3^{28})=
4/22876792454961)x(22876792454961)=
4
A neater looking version can be found on https://www.mathpapa.com/algebra-calculator.html
If this answer is correct, please make me Brainliest.